MANAGEMENT AND DEVELOPMENT OF ABIMANYU LIBRARY COMMUNITY (TBM) IN TULANGAN, SIDOARJO REGENCY - BAKHTIYAR; DANIEL PANDAPOTAN; BAMBANG PRAKOSO (CV KULTURA DIGITAL MEDIA, 2022)
This community service aims to increase public interest in reading by improving the management and development of the Abbimanyu Library community library (TBM) in Tulangan, Sidoarjo Regency. In the implementation of community service using field survey methods and actions by coming to the location, coordinating with the managers involved in the management and development of TBM Abbimanyu Library. Providing materials for the management and development of Community Reading Parks, which in turn provide technical guidance, in order to improve procurement, processing, information distribution, promotion and activities of Community Reading Parks. The management and development method is carried out using the Participatory Rural Appraisal (PRA) approach, which involves more people, namely the involvement of stakeholders, facilitated by